Value-related educational goals of primary school teachers: a comparative study in two European countries - Oeschger, Thomas Peter; Makarova, Elena; Daniel, Ella; Döring, Anna K. (Frontiers in Psychology, 2024)
Schools serve as social institutions that convey values in the context of socialization and enculturation. Teachers are pivotal in this transmission process via their value-related educational goals (VrEGs), which outline how they would like to see their pupils in terms of values. What factors influence these VrEGs? We suggest that those vary on an individual level, but also correspond to the prevailing value orientations of the society.In our study we followed two main goals to test this thesis. Firstly, we examine the differences in VrEGs between teachers of two European countries: Switzerland (CH) and United Kingdom (UK). Secondly, we investigated the similarity of the teachers' VrEGs with prevailing national value orientations from the specific countries.One hundred and fifty primary school teachers (108 CH, 42 UK) were asked about their VrEGs using an adapted version of Schwartz's Portrait Values Questionnaire (PVQ-21). Data from the Human Value Scale (HVS) of the European Social Survey (ESS) was used for countryspecific value orientations. Analyses of the value structures and the differences in value priorities showed that for the individuals from the two countries as well as for the teachers' VrEGs from the two countries, significant differences exist in several value types. Teachers' VrEGs in each country showed a high correlation with the corresponding national value profile.We discuss our results in light of cross-national differences in value education in schools.